2010
DOI: 10.1080/17451001003660293
|View full text |Cite
|
Sign up to set email alerts
|

On the deep-sea Nephasoma species in the Eastern North Atlantic – a taxonomic guide

Abstract: Sipuncula is a relatively species-poor phylum that can play a considerable role in soft sediment benthic ecosystems. The ecological and geochemical influence of sipunculans can vary between species. However, identification of sipunculan species is often problematic. This article focuses on sipunculans collected in the Nordic Seas belonging to the genus Nephasoma, a common genus in deep-water collections. A review of Nephasoma taxonomic descriptions in eastern North Atlantic waters and a key to identifying sipu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 14 publications
0
3
1
Order By: Relevance
“…The complex gallery burrows produced by this species, which can reach 30-50 cm deep in the sediment, and the associated rapid subduction of organic matter are of large importance in the deep sea ecosystems where burrowers are less common than on shelves (Romero-Wetzel 1987;Graf 1989;Shields and Kędra 2009). Although we have not found N. lilljeborgi in this study, and it has not been reported by other authors from the Pacific portion of the Arctic (Murina 1977;Cutler 1994), it is possible that it inhabits deeper portions of the northern Chukchi and Beaufort Seas, and well as the Arctic Basin, as it is an important component of Nordic Seas deep communities (Shields and Kędra 2009;Kędra and Shields 2011). However, more studies are needed in the Pacific sector deep sea to confirm its occurrence and function.…”
Section: Discussioncontrasting
confidence: 46%
See 3 more Smart Citations
“…The complex gallery burrows produced by this species, which can reach 30-50 cm deep in the sediment, and the associated rapid subduction of organic matter are of large importance in the deep sea ecosystems where burrowers are less common than on shelves (Romero-Wetzel 1987;Graf 1989;Shields and Kędra 2009). Although we have not found N. lilljeborgi in this study, and it has not been reported by other authors from the Pacific portion of the Arctic (Murina 1977;Cutler 1994), it is possible that it inhabits deeper portions of the northern Chukchi and Beaufort Seas, and well as the Arctic Basin, as it is an important component of Nordic Seas deep communities (Shields and Kędra 2009;Kędra and Shields 2011). However, more studies are needed in the Pacific sector deep sea to confirm its occurrence and function.…”
Section: Discussioncontrasting
confidence: 46%
“…Species, like N. lilljeborgi and Nephasoma abyssorum, which are typical of Arctic deepsea communities ([1000 m, not sampled here; Kędra and Shields 2011) were not found in this study but are likely to inhabit the Arctic basins. Compared to the northern Bering (four species) and Chukchi (five species) Seas, the two species solely found in the Beaufort Sea seem to indicate an underestimation of Beaufort sipunculan species richness.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations